2017
DOI: 10.1080/15384101.2016.1231284
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic changes of acid-adapted cancer cells push them toward aggressiveness in their evolution in the tumor microenvironment

Abstract: The inter-and intra-tumoral metabolic phenotypes of tumors are heterogeneous, and this is related to microenvironments that select for increased glycolysis. Increased glycolysis leads to decreased pH, and these local microenvironment effects lead to further selection. Hence, heterogeneity of phenotypes is an indirect consequence of altering microenvironments during carcinogenesis. In early stages of growth, tumors are stratified, with the most aggressive cells developing within the acidic interior of the tumor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
48
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(51 citation statements)
references
References 18 publications
3
48
0
Order By: Relevance
“…Moreover, the acidic environment of solid tumors has recently been proposed to provide a niche for dormant cells based on these features [24]. The present study showed that the acid-adapted SW620 cells have stronger tumorigenicity in subcutaneous transplantation model, which is consistent with a previous study showing that the acid adapted breast cancer cells grow faster in vivo [17]. In addition to higher proliferating index, the SW620-AA-originated tumors showed high expression of CA9, reflecting more acidic areas in these tumors.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Moreover, the acidic environment of solid tumors has recently been proposed to provide a niche for dormant cells based on these features [24]. The present study showed that the acid-adapted SW620 cells have stronger tumorigenicity in subcutaneous transplantation model, which is consistent with a previous study showing that the acid adapted breast cancer cells grow faster in vivo [17]. In addition to higher proliferating index, the SW620-AA-originated tumors showed high expression of CA9, reflecting more acidic areas in these tumors.…”
Section: Discussionsupporting
confidence: 92%
“…The acidic-adapted pancreatic cancer cells also tend to take advantage of glutamine to fuel the respiration [16]. Furthermore, it has been reported that the acid-adapted breast cancer cells grow faster in vivo and exhibit invasive phenotype [17].…”
Section: Introductionmentioning
confidence: 99%
“…It’s been known for more than a decade that the center of the ducts in solid cancer models such as breast or prostate cancer is one of the most acidic habitats in the whole tumor ecosystem (Fig 1A) (3, 4, 35). Mechanisms, allowing tumor cells to tolerate acidosis have been studied extensively by our group (4, 36, 37) and others (36, 38).…”
Section: Resultsmentioning
confidence: 99%
“…Assays were conducted in 3D spheroid cultures with varying starting frequencies of each cell type. The spheroid system was selected as an in vitro intermediate between 2D cell culture, which may reach an equilibrium state through confluence rather than resource competition, and in vivo subcutaneous mouse models, which provide less opportunity for replication and frequent monitoring of the two cell populations (27–34). Spheroids were grown in various combinations of pH and glucose concentrations, letting the 3D structure provide natural nutrient and oxygen gradients.…”
Section: Introductionmentioning
confidence: 99%